Meningkatkan Hasil Belajar Prakarya Kerajinan Limbah Lunak dengan Metode Percobaan Siswa Kelas VII C SMPN 14 Samarinda - Nurhasni, Nurhasni (Borneo Research and Education Center, 2021)
This study aims to improve the learning outcomes of crafts on the material of Soft Waste Crafts. This research was carried out in the even semester of the 2021/2022 academic year in class VIIC of SMP Negeri 14 Samarinda which consisted of 34 students. Methods The research was conducted in two cycles with.stages consist of planning, action, observation, and reflection. Activity indicators in the first cycle in good category, in the second cycle in very good category, the results of the formative test of KBM in the first cycle reached 5.89% firs meeting, 44.51% secon meeting, second cycle first meeting 94.12%, 100% second meeting , The results of portfolio in the first cycle were 71.47%, the second cycle was 86.47%. The results of the analysis showed that there was a change in a positive direction or an increase from the two cycles carried out. it can be concluded that the Experimental Model can improve the learning outcomes of Crafts with soft waste craft materials in class VII C of SMPN 14 Samarinda.